Distribution of Ljungan virus in Fennoscandia - Fevola, Cristina; Rossi, Chiara; Hauffe, Heidi Christine; Hörnfeldt, B.; Ecke, F.; Olsson, G.; Magnusson, M.; Miller, A.; Nordström, A.; Henttonen, H.; Niemimaa, J. (2014)
In 1998 a new virus, named ‘Ljungan’ (LV) was isolated in wild populations of bank voles (Myodes glareolus) in Sweden (Niklasson et al, 1998), and soon after in Denmark and the USA. LV is one of two species of the Parechovirus genus within the Picornaviridae family. Interestingly, there is some evidence that LV may cause diabetes-like symptoms in the bank vole and laboratory mouse (Mus musculus). In addition, it has also been suggested that this virus may be associated with human pathologies such as intrauterine fetal deaths (IUFD), CNS malformations (hydrocephaly and anencephaly), and Sudden Infant Death Syndrome (SIDS). Some authors maintain that LV should be considered a potential zoonotic agent (e.g. Greene Macdonald, 2009), while others are distinctly more sceptical (e.g. Hindersson et al., 2005; Krous et Langlois, 2009; Tapia et al., 2010). Recent optimization and testing of a serological test show that humans can be infected with LV (Jääskeläinen et al 2013). One hypothesis is that the bank vole and other rodents could act as reservoirs and/or vectors of LV. Therefore, knowledge of LV’s geographical and host range is crucial to assessing its potential importance as human pathogen and identifying zoonotic reservoirs. Tissue samples are currently being collected from rodents across the EU as part of the EU FP7 project EDENext and ongoing molecular studies suggest that LV has a wide geographical and host distribution, including commensal species. Here we present recent results of the distribution of the virus in 457 samples (17 sites) across Sweden and Finland, one of the most intensive prevalence studies conducted thus far. These results suggest that LV has a focal distribution along the coast. Future studies will include comparative phylogenomics and identification of possible strains of LV, as well as temporal variation in infection, mode of transmission, and ecological (biotic and abiotic) correlations